Does Relative Income Matter? Are the Critics Right? - Richard Layard; Guy Mayraz; Stephen Nickell (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Do other peoples' incomes reduce the happiness which people in advanced countries experience from any given income? And does this help to explain why in the U.S., Germany and some other advanced countries, happiness has been constant for many decades? The answer to both questions is "Yes". We provide 4 main pieces of evidence. 1) In the U.S. General Survey (repeated samples since 1972) comparator income has a negative effect on happiness equal in magnitude to the positive effect of own income. 2) In the West German Socio-Economic Panel since 1984 the same istrue but with life satisfaction as the dependant variable. We also use the Panel to compare the effect of income comparisons and of adaptation as factors explaining the stable level of life-satisfaction: income comparisons emerge as much the more important. 3) When in our U.S. analysis we introduce "perceived" relative income as a potential explanatory variable, its effect is as large as the effect of actual relative income - further supporting the view that comparisons matter. 4) Finally, for a panel of European countries since 1973 we estimate the effect of average income upon average lifesatisfaction, splitting income into two components: trend and cycle. The effect of trend income is small and illdefined. Our conclusions relate to time series and to advanced countries only. They differ from those drawn in recent studies by Deaton and Stevenson/Wolfers, but those studies are largely cross-sectional and mostly include non-advanced as well as advanced countries.
Keywords: D31; D90; E1; H0; I31; O15; 330; Easterlin Paradox; happiness; relative income; growth